How Plutonium Undermines the Hibakusha - Kibaroğlu, Mustafa (Bulletin of the Atomic Scientists, 2015)
Akira Kawasaki wrote in Round One that the noble disarmament efforts of the Hibakusha—survivors of the atomic bombings of Hiroshima and Nagasaki—"have often been ignored" outside Japan. Indeed, the Hibakusha's message has "sometimes been misinterpreted so badly" that it has "been portrayed as an incentive for nations to develop nuclear weapons in the name of deterrence."
Keywords: Nuclear Weapons; Nuclear Energy